(untitled) (Fiep Bulletin - online, 2014)
The motive loss of march in individuals with Parkinson’s disease in the group for a literary abyss. Individuals with Parkinson’s disease are attacked severely in the march. This study aims at to verify the use of aquatic exercises as strategy of march improvement in individuals with Parkinson’s disease. Used 02 individuals, male, with age among 35/40 years with treatment in Cemeaes (Macaé, RJ, Brazil), for 12 months. The result doesn’t demonstrate improvement of the march. Was ended that aquatic rehabilitation through the aquatic exercises, doesn’t favor the march in individuals with Parkinson’s disease.